MIGRATION, CULTURAL IDENTITY, AND COPING MECHANISMS IN A GLOBALIZED WORLD - Ganiev, Akhrorjon (Журнал Педагогики и психологии в современном образовании, 2024)
Migration in this modern-day globalized world serves as a complex challenge toward both cultural identity and psychological well-being. In such cases, migrants try to keep up a balance between maintaining their cultural identity and successfully assimilating into the host societies. The review explores literature related to the triangulation of migration, cultural identity, and coping mechanisms through the lens of cultural psychology and migration studies. Discussion in this article centers on how cultural identity is shaped, transformed, or threatened in relation to migration and how migrants cope with such changes in their cultural identity. A focus on acculturation theory, identity negotiation, and coping frameworks offers insights into migrants’ psychological resiliency. The following literature-based analysis tries to bring together cultural psychology and research on migration by providing a comprehensive understanding of the way people maintain or reshape their cultural identity in a widely interconnected world.